The social disappearance of differences in exception policies: the lives and memories of children and women for the reinvention of democratic education - Salgado, Raquel Goncalves; Souza, Leonardo Lemos de [UNESP] (Editora Univ Federal Parana, Centro Politecnico, 2020)
Democracy has been a recurrent theme in Brazil for the past decade, due to the emergence of conservative narratives and movements that prohibit public debate on issues that bring differences to the social field, such as racism and gender and sexual violence, in addition to calling for the reissue of exception policies during the civic-military dictatorship in Brazil. Thus, the main objective of this article is to analyze the meanings of democracy and education based on incursions into the past of the military dictatorship, as a way of problematizing the exception policies in force in Brazil today. Therefore, we intend to discuss: (1) the necropolitics that affected the lives of children and women in the military dictatorship, based on testimonies about tortures practiced by State agents, extracted from the report of the National Truth Commission, and their relations with necropolitics in Brazil today that refer to racism and gender violence, based on criticisms of the notions of protection and development in their colonizing effects; and (2) the social disappearance as a policy for exterminating memory and its harmful repercussions on education. Finally, we seek to highlight the devastating process of differences, whether gender, sexual, racial, ethnic and age, implemented by past and present exception policies, and as a democratic education, which stands against these policies, can be a resistance to barbarism.
Keywords: Feminisms; Childhoods; Military dictatorship; Democracy; Education